Exploring the politics of strain: Crime and welfare in remote Indigenous Australia. (21st October 2021) - Staines, Zoe; Zahnow, Renee
Abstract: The international criminology and social policy literature have long explored possible connections between social welfare and crime. However, existing studies tend towards high‐level comparisons of crime versus total aggregate welfare spend, overlooking sub‐national contextual differences between and within countries. There are also few studies that deeply explore this link in the Antipodes, including in Australia: a settler colony and (neo)liberal welfare state with a recent strong coupling of punitive social and penal policies that disproportionately impact Indigenous populations. This paper attends to these gaps by examining the welfare‐crime link in remote Indigenous Queensland (Australia). We use crime‐report data and an interrupted time series design to explore the effects of dynamic social welfare policies during 2020–20 21: a period that saw a temporary shift away from a strict neoliberal welfare model (i.e., heavy conditionality, low benefit rates) to more supportive and decommodifying social welfare in response to the COVID‐19 induced economic recession. Our findings align with previous studies that suggest more supportive and decommodifying policies are associated with lower crime. We also bring greater nuance to how the crime‐welfare link is understood within the 'structural complexity of [Australian] settler colonialism' (Wolfe. Journal of Genocide Research . 2006;8:392), by illuminating how a politics of race animates social policies that can either produce or reduce criminogenic strains and, thus, socially construct crime in the image of the Indigenous 'Other'.